High Thermal Conductivity Silicone Elastomer Doped with Graphene Nanoplatelets and Eutectic GaIn Liquid Metal Alloy. (1st January 2019) - Sargolzaeiaval, Yasaman; Ramesh, Viswanath Padmanabhan; Neumann, Taylor V.; Miles, Rebecca; Dickey, Michael D.; Öztürk, Mehmet C.
Abstract : This paper reports the thermal conductivity and mechanical properties of Sylgard 184 polydimethylsiloxane (PDMS) elastomer loaded with graphene nano-platelets (GnPs) and eutectic Ga-In (EGaIn) liquid metal droplets. We fabricated samples with different GnP and EGaIn concentrations and measured their thermal conductivity using the steady-state absolute technique. The results show that the thermal conductivity of the elastomer can be enhanced up to 5.6X when both GNP and EGaIn are included in the elastomer. Without EGaIn, the enhancement is limited to 4.4X. The results suggest that EGaIn inclusion did not change the viscosity of the uncured material significantly at any GnP loading level. We also observed that addition of just EGaIn to PDMS did not have a significant impact on the material's stiffness while lowering its ultimate tensile strength by a factor of 2X and the maximum elongation at the break point by a factor of 1.6X. On the other hand, it was demonstrated that GnP addition to pure PDMS or EGaIn doped PDMS made the elastomer stiffer and less tear resistant with lower elongation at the break point.